Arduino-based control and monitoring system for minimum material weight on Belt conveyor Dosimat Fedder at PT. Semen Padang - Albaihaky, Rahul; Mirshad, Emilham (Journal of Industrial Automation and Electrical Engineering, 2025)
The Dosimat feeder is a device used to accurately weigh additional materials before they enter the mill for the grinding process. The Dosimat feeder adjusts the material weight by increasing the motor speed when the hopper does not release supplementary materials such as gypsum. This research employs the Research and Development (R&D) method, which aims to produce a specific product and test its effectiveness. The results show that the measured weight data is displayed on a 16x2 LCD via an I2C module. A buzzer activates when the material weight drops below 331 grams, and the motor stops until the minimum weight is reached. Testing indicates that the load cell has an average accuracy of 98% (with an error margin of 0.6%–5%) for weights ranging from 100 to 400 grams. Motor speed decreases from 32 rpm (at 360 grams) to 21 rpm (at 480 grams) as the load increases. The system operates optimally when Dosimat 2 and 3 are active and all three LEDs are on, thereby improving production efficiency and preventing losses due to material shortages.